AB0755 Depression and anxiety may contribute to higher disease activity and worse quality of life in psoriatic arthritis. (15th June 2017) - Farkas, F; Ikumi, N; Szentpetery, A; Kirby, B; FitzGerald, O
Abstract : Background: Psoriatic arthritis (PsA) is a heterogeneous disease with variable types of joint involvement, extra-articular features, including skin psoriasis, and with well-known comorbidities such as depression and anxiety 1 . Composite Psoriatic Disease Activity Index (CPDAI) adequately assesses disease activity in this complex condition 2 . To date, no study has evaluated the relationship between depression/anxiety scores and CPDAI in PsA. Objectives: The aim of this study was to compare 1) depression/anxiety scores; 2) physician-assessed and patient-reported outcome measures (PROMs) between patients with CPDAI≤4 suggesting low disease activity versus with CPDAI>4 reflecting moderate or severe disease activity in PsA. Methods: PsA patients fulfilling the CASPAR criteria were recruited. Patients underwent musculoskeletal and skin assessments (TCJ68, SJC66, Leeds enthesitis index, dactylitis digit score and PASI) and they have completed questionnaires on physical function and health-related quality of life (HAQ, PsAQoL, DLQI, EQ-5D, BASDAI, BASFI, ASQoL, BRAF-NRS, pain and general health VAS). Patients were assessed for depression/anxiety using the Hospital Anxiety and Depression Scale (HADS-A and HADS-D) and Penn State Worry Questionnaire (PSWQ). Data were analyzed using Mann Whitney, Chi-square tests and linear regression model. Results: 100 PsA patients were recruited; 57 presented with CPDAI≤4 (age 52.7±9.46 years) and 43 with CPDAI>4 (age 52±11.82 years). Patients with CPDAI>4 had significantly higher TCJ68 (p<0.001), Leeds enthesitis index (p=0.015) and significantly worse HAQ, BASDAI and ASQoL scores. There was no significant difference in other items of CPDAI between the two groups. Patients with CPDAI>4 had significantly higher HADS-D, HADS-A and PSWQ scores (p<0.001; p<0.001; p=0.001, respectively) and significantly worse PROMs, including PsAQoL, EQ-5D score, BASFI, BRAF-NRS, pain and general health VAS (Table 1 ). Multiple regression analysis revealed significant relationship between PsAQoL, BASFI and CPDAI (B=0.311, p=0.0093; B=0.568, p<0.0001, respectively). Conclusions: This is the first study assessing the relationship betweeen depression/anxiety and CPDAI in PsA. We have found significantly higher HADS-D, HADS-A, PSWQ scores and worse PROMs in patients with CPDAI>4 compared to those with CPDAI≤4. Based on our results there is significant relationship between depression/anxiety, physical function, quality of life and disease activity in psoriatic arthritis. References: Haroon M. Expert Rev Clin Immunol. 2016. Mumtaz A. Ann Rheum Dis. 2011. Disclosure of Interest: F. Farkas: None declared, N. Ikumi: None declared, A. Szentpetery: None declared, B. Kirby Grant/research support from: Abbvie, O. FitzGerald Grant/research support from: Abbvie, Pfizer, BMS, Consultant for: Abbvie, Pfizer, BMS, Novartis, Celgene, Janssen, UCB, Eli Lilly